Growth and chemical profile of clary sage (Salvia sclarea L.) in response to algae and banana peel extracts - El-Gohary, Ahmed E. (2023)
The highest values of fresh and dry weights were detected with the treatment of 1.5 g/l (BPW) × 1.5 g/l (ALS). The maximum inhibition of free radical -cavenging activity was recorded at 1 g/l (ALS) × 0.5 g/l (BPW). 2 g/l (ALS) without BPW treatment resulted in the greatest amounts of total carbohydrates. The greatest accumulation of total flavonoids was obtained from the plants treated with 0.5 g/l (BPW) × 1 g/l (ALS). Plants exposed to 1.5 g/l (BPW) with 2 g/l (ALS) gave the greatest accumulation of total phenols. Phenolic compounds that were detected by HPLC analysis were changed due to ALS, BPW, and their interactions.